HIV drug resistance levels in adults failing first‐line antiretroviral therapy in an urban and a rural setting in South Africa. Issue 2 (28th June 2016) - Rossouw, TM; Nieuwoudt, M; Manasa, J; Malherbe, G; Lessells, RJ; Pillay, S; Danaviah, S; Mahasha, P; van Dyk, G; de Oliveira, T
Abstract : Objectives: Urban and rural HIV treatment programmes face different challenges in the long‐term management of patients. There are few studies comparing drug resistance profiles in patients accessing treatment through these programmes. The aim of this study was to perform such a comparison. Methods: HIV drug resistance data and associated treatment and monitoring information for adult patients failing first‐line therapy in an urban and a rural programme were collected. Data were curated and managed in SATuRN RegaDB before statistical analysis using Microsoft Excel 2013 andstata Ver14, in which clinical parameters, resistance profiles and predicted treatment responses were compared. Results: Data for 595 patients were analysed: 492 patients from a rural setting and 103 patients from an urban setting. The urban group had lower CD4 counts at treatment initiation than the rural group (98 vs . 126 cells/ μ L, respectively; P = 0.05), had more viral load measurements performed per year (median 3 vs . 1.4, respectively; P < 0.01) and were more likely to have no drug resistance mutations detected (35.9% vs . 11.2%, respectively; P < 0.01). Patients in the rural group were more likely to have been on first‐line treatment for a longer period, to have failed for longer, and to have thymidine analogue mutations. Notwithstanding these differences, the two groups had comparable predicted responses to the standard second‐line regimen, based on the genotypic susceptibility score. Mutations accumulated in a sigmoidal fashion over failure duration. Conclusions: The frequency and patterns of drug resistance, as well the intensity of virological monitoring, in adults with first‐line therapy failure differed between the urban and rural sites. Despite these differences, based on the genotypic susceptibility scores, the majority of patients across the two sites would be expected to respond well to the standard second‐line regimen.